1990
DOI: 10.1002/chin.199001205
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: The Chemistry of 2H‐3,1‐Benzoxazine‐2,4(1H)‐dione (Isatoic Anhydride). Part 21. A Mild Process for the Application of 10‐Alkyl‐9‐acridanones and Its Application to the Synthesis of Acridone Alkaloids.

Abstract: 10‐Substituted‐9‐acridanones such as (IV) are readily prepared by the reaction of the isatoic anhydride (I) with 2‐cyclohexenone (II) and subsequent aromatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…We recognized that NEt 3 and DBU would be inadequate to deprotonate the cycloalkanones. Historically, LDA 25 or TMEDA/n-BuLi 14 has been employed (Figure 3) with mixed results to build compounds of this type. Seeking a less air-sensitive, readily available base capable of deprotonating these substrates, commercially available LiHMDS was evaluated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recognized that NEt 3 and DBU would be inadequate to deprotonate the cycloalkanones. Historically, LDA 25 or TMEDA/n-BuLi 14 has been employed (Figure 3) with mixed results to build compounds of this type. Seeking a less air-sensitive, readily available base capable of deprotonating these substrates, commercially available LiHMDS was evaluated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Coppola et al showed that acridines (i.e., fully aromatized versions of 22) could be prepared by generating and then oxidizing cyclohexene-fused-4-quinolinones 22. 25 The study only described the isolation of two examples of 22 in modest yields when cyclohexanone 21a, deprotonated with lithium diisopropylamide (LDA), was treated with isatoic anhydrides 20. Cycloalkane-fused quinolinones 24a,b have been prepared by two protocols.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Similar observations have been made with anilines having exceptional electron density due to multiple oxygen substituents. 7 Treatment of 21 with oxalyl chloride produced compounds 22 and 23. These were presumed to have been formed from the intermediate shown, which leads to 23 by a Fries 8 type rearrangement and to 22 by a von Braun 9 dealkylation, followed by an internal cyclization.…”
Section: Chemistrymentioning
confidence: 99%
“…The mixture was extracted with CH2Cl2/2-propanol (3:1). The organic layer was washed with brine, dried over Na2SO4, and evaporated at reduced pressure to give 3.0 g (yield 52%) of 3-(2-amino-1,2dioxoethyl)-2-ethyl-5-methoxy-1H-indole (7). This material (12.2 mmol) was dissolved in 25 mL of THF and 125 mL of DMSO and stirred with 520 mg of NaH (60% in mineral oil; 13 mmol) for 15 min, and then with 1.6 mL (13 mmol) of benzyl bromide for 45 min.…”
Section: -[[3-(2-amino-12-dioxoethyl)-2-ethyl-1-(phenylmethyl)-1h-ind...mentioning
confidence: 99%
“…Both N-methyl- 37 and N-ethyl-3,4,5-trimethoxyaniline 19 were synthesized by direct alkylation with methyl Nucleophilic displacement of the bromide 22 (Scheme 1) with N-methyl-3,4,5-trimethoxyaniline afforded the dipivaloylated compound 23 which was deprotected to afford the desired N-methyl derivative 3 in 48% yield from bromide 22. A similar nucleophilic displacement with N-ethyl-3,4,5-trimethoxyaniline afforded the protected derivative 24.…”
Section: Chemistrymentioning
confidence: 99%